Mexican Fruit Fly, Anastrepha ludens (Loew) (Insecta: Diptera: Tephritidae) - Howard V. Weems, Jr.; John B. Heppner; Gary L. Steck; Thomas R. Fasulo; James L. Nation (EDIS, 2004)
The Mexican fruit fly, Anastrepha ludens (Loew), is a very serious pest of various fruits, particularly citrus and mango, in Mexico and Central America. Its natural distribution includes the Rio Grande Valley of Texas, where populations routinely attain pest status if control measures are not practiced. It is a frequent invader in southern California and Arizona. Mexican fruit fly represents a particular threat to Florida because of its special affinity for grapefruit, of which Florida is one of the world's leading producers. This document is EENY-201 (originally published as DPI Entomology Circulars 16, 260 and 391), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: March 2001. Revised: June 2003, January 2004.